Effect of a 3-Weeks Training Camp on Muscle Oxygenation, V˙O2 and Performance in Elite Sprint Kayakers - Paquette, Myriam; Bieuzen, François; Billaut, François (Frontiers in Sports and Active Living, 2020)
Purpose: Peripheral adaptations, as assessed via near-infrared spectroscopy (NIRS) derived changes in muscle oxygenation (SmO2), are good predictors of sprint kayak performance. Therefore, the goal of the present study was to assess changes in SmO2 and V˙O2 following a training camp in elite sprint kayakers to evaluate if the training prescribed elicits peripheral adaptations, and to assess associations between training-induced changes in physiological responses and performance. Methods: Eight male elite sprint kayakers, members of the Canadian National Team, performed a 200-m and 1,000-m on-water time trial (TT) before and after a 3-weeks winter training camp. Change in performance, V˙O2 and SmO2 of the biceps brachii were assessed in relation to training load. Results: Training load and intensity were increased by ~20% over the course of the training camp, which resulted in a 3.7 ± 1.7% (ES 1.2) and 2.8 ± 2.4% (ES 1.3) improvement in 200-m and 1,000-m performance, respectively. Performance improvement in the 200-m was concomitant to a reduced SmO2, an increased V˙O2 peak and an increased reoxygenation rate after the TT. The 1,000-m TT performance improvement was concurrent with a reduced SmO2 in the last half of the TT and an increased V˙O2 in the first minute of the TT. Conclusion: Our results strongly suggest that peripheral skeletal muscle adaptations occurred in these athletes with the proposed training plan. This further attests the benefit of using portable NIRS as a monitoring tool to track training-induced adaptations in muscle oxygen extraction in elite athletes.